The Relationship Between the Intensity of Gadget Use at Home and Students' Discipline at School: A Study of Elementary School Students - Masitoh, Leli; Widiarti, Nuni; Sumartiningsih, Sri; Wasino, Wasino; Aricindy, Argitha; Eko Armaidi, Indriana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
This research to determine the relationship between gadget use at home and the disciplinary attitudes of elementary school students in the school environment. The research used a quantitative approach with a correlational research type. The research population was third-grade students of Margajaya 2 Elementary School and their parents in the 2025/2026 academic year. Data were collected using two types of questionnaires, namely a gadget use questionnaire filled out by parents and a discipline attitude questionnaire filled out by students. Before the correlation test was carried out, the data were first tested for normality using Shapiro-Wilk. The results of the normality test showed that the data were not normally distributed (Sig. <0.05), so the correlation analysis was carried out using the Spearman Rank correlation test. The results showed a correlation coefficient of 0.121 with a significance value of 0.538 (p>0.05). These results indicate that the relationship between gadget use at home and students' disciplinary attitudes is in the very low and insignificant category. Thus, it can be concluded that there is no significant relationship between gadget use at home and students' disciplinary attitudes at school. It is thought that students' disciplinary attitudes are more influenced by other factors such as parenting patterns, family environment, learning habits, and the role of teachers at school.